Improvement of the Nurses' Awareness toward Ventilator-Associated Pneumonia Based on Evidence Guidelines - Zainab Mohamed ALaswad; Magda Bayoumi (Indian Journal of Medical Specialities)
Background: Ventilator Associated Pneumonia (VAP) is a common hospital acquired infection that occurs as complication in patients who are connected to Mechanical Ventilation (MV). Nurses in intensive care unit (ICU) should be updated with the latest evidence-based practice to prevent such complication. This study aimed to assess improvement of the nurses' awareness toward ventilator-associated pneumonia based on latest evidence guidelines. Methods: A quantitative pretest-posttest design has been conducted. Using a convenience sample of 58 nurses who are working in the ICU were recruited. Tools: A self-administrative questionnaire was adapted to assess the nurse's knowledge about VAP and VAP prevention bundle. Results: The results highlighted that all ICU nurses had improvement of knowledge level pre-post regarding VAP (p <0.001), VAP prevention (p <0.001), and the overall knowledge score improvement revealed significantly higher after the educational program (p <0.001). Conclusion: Periodic refreshing on-services education program should be provided to nurses in ICU to improve their knowledge and to maintain high level of information, moreover hospital policies should include updated guidelines for VAP prevention bundle and protocol from international evidence.